Edukasi Alokasi Keuangan untuk Asuransi Kesehatan pada Mahasiswa - Wulandari, Mas Siti Rifani; Hilaliyah, Bulan; Elnora, Farisa Dwi; Nurbidari, Indri; Simanjuntak, Megawati (Institut Pertanian Bogor, 2023)
The Covid-19 pandemic has made people aware of the importance of staying healthy and protecting themselves before the disease strikes. The Health Insurance Funding Educational Campaign is a program designed to increase the knowledge of college students so they can properly allocate their finances. Educational delivery was conducted online via Zoom Meeting with 36 participants. Due to the PSBB (Large-Scale Social Restrictions) program to prevent the spread of Covid-19, the education was conducted in Zoom meetings. The method includes lecture, discussion and assessment by completing pre- and post-tests. This material explains the urgency of insurance during this time. The educational activities resulted in participants' increased knowledge of health insurance and proper financial attribution, as reported by completing pre-and post-tests. The implementation of these educational activities has encountered some obstacles, such as the inability of the event organizers to directly monitor each participant so that they can keep an eye on the process of the event.